STD‐NMR‐Based Protein Engineering of the Unique Arylpropionate‐Racemase AMDase G74C. Issue 13 (16th July 2015) - Gaßmeyer, Sarah Katharina; Yoshikawa, Hiroyuki; Enoki, Junichi; Hülsemann, Nadine; Stoll, Raphael; Miyamoto, Kenji; Kourist, Robert
Abstract Structure‐guided protein engineering achieved a variant of the unique racemase AMDase G74C, with 40‐fold increased activity in the racemisation of several arylaliphatic carboxylic acids. Substrate binding during catalysis was investigated by saturation‐transfer‐difference NMR (STD‐NMR) spectroscopy. All atoms of the substrate showed interactions with the enzyme. STD‐NMR measurements revealed distinct nuclear Overhauser effects in experiments with and without molecular conversion. The spectroscopic analysis led to the identification of several amino acid residues whose substitutions increased the activity of G74C. Single amino acid exchanges increased the activity moderately; structure‐guided saturation mutagenesis yielded a quadruple mutant with a 40 times higher reaction rate. This study presents STD‐NMR as versatile tool for the analysis of enzyme–substrate interactions in catalytically competent systems and for the guidance of protein engineering.